Modelling of marine ecosystem in regional scale for short term prediction of satellite-aided operational fishery advisories. (20th November 2019) - Chakraborty, Kunal; Maity, Sourav; Lotliker, Aneesh A.; Samanta, Alakes; Ghosh, Jayashree; Masuluri, Nagaraja Kumar; Swetha, Naga; Bright, Rose P.
ABSTRACT: The operational Potential Fishing Zone (PFZ) advisory generated and disseminated by the ESSO-Indian National Centre for Ocean Information Services has a significant impact on the livelihood of coastal community of India. PFZs are identified as the relatively narrow zones in the ocean where horizontal gradients of physical and/or biological properties are enhanced. The advisories are provided to fishermen on a daily basis using remotely sensed sea surface temperature (SST) and chlorophyll-a (Chl-a) data from NOAA-AVHRR and MODIS-AQUA and/or Oceansat-2 satellites, respectively. Sometimes it becomes a major challenge to retrieve SST/Chl-a data from satellite images, particularly during the extensive cloud coverage. To overcome this operational difficulty, the satellite data is replaced by a coupled physical-biogeochemical model data capable of simulating ocean features leading to PFZs. The use of model data provides an additional advantage towards transforming the existing service from advisories to forecast. The average length of PFZs identified from satellite (model) data (2010–2016) for off Gujarat is 27.80 ± 7.2 km (33.07 ± 3.2 km) whereas for off Andhra Pradesh, it is 28.27 ± 10.9 km (52.48 ± 8.7 km). Considering the capability of the model in identifying PFZs, the existing advisory service can be transitioned into a short term PFZ forecast.